2014
DOI: 10.1111/emr.12093
|View full text |Cite
|
Sign up to set email alerts
|

Fish passage in the Murray‐Darling Basin, Australia: Not just an upstream battle

Abstract: Summary Construction of instream barriers, preventing fish from accessing spawning, nursery and feeding habitat, is a major issue impacting fisheries sustainability throughout the world. Since European settlement, development in the Murray-Darling Basin for irrigation and potable water supplies has led to the construction of over 10,000 barriers to fish movement. The Native Fish Strategy listed fish passage as a major driving action and was proactive in progressing cost-effective solutions to help inform large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 60 publications
2
71
0
Order By: Relevance
“…However, the concept that migration routes for fish can be universally reinstated through the installation of fishways resulting from the transfer of expertise and infrastructure between and within geographical regions has generated substantial debate (Kemp, ). Some successes have been reported (Barrett & Mallen‐Cooper, ; Baumgartner, Zampatti, Jones, Stuart, & Mallen‐Cooper, ; Parsley et al., ), especially at sites where solutions were specifically developed to meet target species and hydrology. But the precarious conservation status of native population reduction of migratory species in South America (Agostinho, Gomes, Fernandes, & Suzuki, ; Agostinho, Gomes, & Latini, ), and the disrupted river connectivity throughout Africa (Jewitt, Goodman, Erasmus, O'Connor, & Witkowski, ; Nel et al., ; Wasserman, Weyl, & Strydom, ) and Asia (Dudgeon, ), clearly indicates that these strategies cannot be applied everywhere.…”
Section: Translation Of Fish Passage Expertise and Infrastructure Betmentioning
confidence: 99%
“…However, the concept that migration routes for fish can be universally reinstated through the installation of fishways resulting from the transfer of expertise and infrastructure between and within geographical regions has generated substantial debate (Kemp, ). Some successes have been reported (Barrett & Mallen‐Cooper, ; Baumgartner, Zampatti, Jones, Stuart, & Mallen‐Cooper, ; Parsley et al., ), especially at sites where solutions were specifically developed to meet target species and hydrology. But the precarious conservation status of native population reduction of migratory species in South America (Agostinho, Gomes, Fernandes, & Suzuki, ; Agostinho, Gomes, & Latini, ), and the disrupted river connectivity throughout Africa (Jewitt, Goodman, Erasmus, O'Connor, & Witkowski, ; Nel et al., ; Wasserman, Weyl, & Strydom, ) and Asia (Dudgeon, ), clearly indicates that these strategies cannot be applied everywhere.…”
Section: Translation Of Fish Passage Expertise and Infrastructure Betmentioning
confidence: 99%
“…Indeed, the MDB rates amongst the most highly affected river basins in the world with only 40–50% of its water course length remaining free‐flowing (Liermann et al , ). It is suggested that >10 000 barriers have been constructed on MDB rivers and floodplain channels that pose barriers to fish passage (Baumgartner et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It included a significant multijurisdictional monitoring programme, which has resulted in continual adaptive, cost‐effective improvement of fishway designs and approaches (Baumgartner et al . ). Most fishways have been fitted with an automated PIT (Passive Integrated Transponder) telemetry system to assess the effectiveness of the fishways with more than 35 000 fish tagged and now at liberty along the river Murray (Barrett ).…”
Section: Key Achievementsmentioning
confidence: 97%